Fc Gamma Receptors and Complement Component 3 Facilitate Anti-fVIII Antibody Formation - Zerra, Patricia E.; Arthur, Connie M.; Chonat, Satheesh; Maier, Cheryl L.; Mener, Amanda; Shin, Sooncheon; Allen, Jerry William L.; Baldwin, W. Hunter; Cox, Courtney; Verkerke, Hans; Jajosky, Ryan P.; Tormey, Christopher A.; et al. (Frontiers in Immunology, 2020)
Anti-factor VIII (fVIII) alloantibodies, which can develop in patients with hemophilia A, limit the therapeutic options and increase morbidity and mortality of these patients. However, the factors that influence anti-fVIII antibody development remain incompletely understood. Recent studies suggest that Fc gamma receptors (FcgRs) may facilitate recognition and uptake of fVIII by recently developed or pre-existing naturally occurring anti-fVIII antibodies, providing a mechanism whereby the immune system may recognize fVIII following infusion. However, the role of FcgRs in anti-fVIII antibody formation remains unknown. In order to define the influence of FcgRs on the development of anti-fVIII antibodies, fVIII was injected into WT or FcgR knockout recipients, followed by evaluation of anti-fVIII antibodies. Anti-fVIII antibodies were readily observed following fVIII injection into FcgR knockouts, with similar anti-fVIII antibody levels occurring in FcgR knockouts as detected in WT mice injected in parallel. As antibodies can also fix complement, providing a potential mechanism whereby anti-fVIII antibodies may influence anti-fVIII antibody formation independent of FcgRs, fVIII was also injected into complement component 3 (C3) knockout recipients in parallel. Similar to FcgR knockouts, C3 knockout recipients developed a robust response to fVIII, which was likewise similar to that observed in WT recipients. As FcgRs or C3 may compensate for each other in recipients only deficient in FcgRs or C3 alone, we generated mice deficient in both FcgRs and C3 to test for potential antibody effector redundancy in anti-fVIII antibody formation. Infusion of fVIII into FcgRs and C3 (FcgR x C3) double knockouts likewise induced anti-fVIII antibodies. However, unlike individual knockouts, anti-fVIII antibodies in FcgRs x C3 knockouts were initially lower than WT recipients, although anti-fVIII antibodies increased to WT levels following additional fVIII exposure. In contrast, infusion of RBCs expressing distinct alloantigens into FcgRs, C3 or FcgR x C3 knockout recipients either failed to change anti-RBC levels when compared to WT recipients or actually increased antibody responses, depending on the target antigen. Taken together, these results suggest FcgRs and C3 can differentially impact antibody formation following exposure to distinct alloantigens and that FcgRs and C3 work in concert to facilitate early anti-fVIII antibody formation.